1983
DOI: 10.1016/0736-5748(83)90213-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic testosterone increase in the male rat at birth

Abstract: In the male rat, a dramatic increase in serum testosterone occurs during the first 2 h of postnatal life. Since the hypothalamus is known to be an important site for sexual differentiation of the brain, this early testosterone surge was a good model to use to study the transfer of serum testosterone to the hypothalamus and cerebral cortex. Endogenous testosterone was measured by radioimmunoassay in the hypothalamus and the cerebral cortex of the foetus and newborn rats during the first 6 h following birth. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…9"1° In contrast, aromatase activity is very low in the cerebral cortex. 9"15 Rhoda et al 26 reported that hypothalamic testosterone increased during the first 2 h of postnatal life in male rats. The increase was not detected in female rats and in males gonadectomized in utero, and the hypothalamus showed an affinity for testosterone at birth, which was not found in the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…9"1° In contrast, aromatase activity is very low in the cerebral cortex. 9"15 Rhoda et al 26 reported that hypothalamic testosterone increased during the first 2 h of postnatal life in male rats. The increase was not detected in female rats and in males gonadectomized in utero, and the hypothalamus showed an affinity for testosterone at birth, which was not found in the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis, first proposed in the seminal 1959 paper by Phoenix et al [110], has proven to be an essential principle of sexual differentiation, though evidence now indicates that a few sex differences are governed by differences in genes on the sex chromosomes [9]. From late fetal life through early postnatal life, male rodents have significantly higher circulating T of gonadal origin than their female littermates [25; 93; 154] and this T travels to and acts in the brain [119]. It is believed that this circulating perinatal T is critical for directing most sex differences in the brain, though in most cases, it is actually E2, produced locally in the brain by aromatization from the circulating T, that is ultimately responsible for organizing neural sex differences.…”
Section: Development Of the Rodent Avpv/pen Kisspeptin Systemmentioning
confidence: 99%
“…In most species, the testosterone surge is relatively transient with levels declining within hours [6]; however, in some species such as non-human primates and humans, the elevations in testosterone may persist for many hours to weeks following birth [6,10,11]. The elevation in plasma testosterone quickly increases testosterone levels in the hypothalamus [14,15]. In rats, castration shortly after birth prevents the elevation of testosterone levels in the hypothalamus, indicating that the testes are the primary source of the rise in plasma testosterone [14].…”
Section: Introductionmentioning
confidence: 99%
“…The elevation in plasma testosterone quickly increases testosterone levels in the hypothalamus [14,15]. In rats, castration shortly after birth prevents the elevation of testosterone levels in the hypothalamus, indicating that the testes are the primary source of the rise in plasma testosterone [14]. Through the aromatization of testosterone by the enzyme P450 aromatase (CYP19A1), oestradiol levels within the hypothalamus are elevated [15].…”
Section: Introductionmentioning
confidence: 99%